The Conceptual Framework to Achieve Energy Consumption Balance in Kuala Lumpur Shophouses for Mitigating Urban Heat Island Effects with Focusing On Anthropogenic Heat Factor - Shahmohamadi, P.; Che-Ani, A.I.; Tawil, N.M.; Maulud, K.N.A.; Tahir, M.M. (Journal of Surveying, Construction and Property, 2011)
Shophouses represent important land uses in Kuala Lumpur since many years ago, which influence the resulting thermal environment including the formation of urban heat island (UHI). Production of anthropogenic heat and using energy for cooling systems, lighting and etc. in shophouses led to have serious impacts on the thermal environmental quality such as quality of the air, increase in temperature, energy consumption and finally the formation of UHI. An attempt to study and observe the problems of Kuala Lumpur shophouses has been made, using conceptual framework to understand the correlation among increasing the intensity of UHI, the production of anthropogenic heat and energy consumption. This paper literately investigates the impact of Urban Heat Island (UHI) on energy consumption and also determines which factors can directly affect energy use in shophouses with focus on anthropogenic heat factor and finally suggests three important strategies to minimise the impact of UHI on energy consumption: promoting natural ventilation of shophouses, using appropriate materials on external surfaces and providing appropriate greenery. Keywords: Anthropogenic Heat, Energy Consumption Balance, Kuala Lumpur Shophouses, Urban Heat Island.